2001
DOI: 10.1094/pdis.2001.85.8.921a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Beech Bark Disease in Michigan

Abstract: Beech bark disease of American beech (Fagus grandifolia) is caused by the interaction of an introduced scale insect (Cryptococcus fagisuga) and the native fungus Nectria galligena, or N. coccinea var. faginata, which is thought to be introduced. Infestations of the insect precede development of the disease, and N. galligena is often found before N. coccinea var. faginata. Previously published records indicate that the beech scale extends as far west as eastern Ohio (2) and southern Ontario (Sajan, personal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Since its discovery in North America, the seriousness of beech bark disease has varied and it has continued to spread southward (Houston 1994a). In the last few years, it has also spread westward into Ohio and Michigan (O'Brien et al 2001;MacKenzie and Iskra 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in North America, the seriousness of beech bark disease has varied and it has continued to spread southward (Houston 1994a). In the last few years, it has also spread westward into Ohio and Michigan (O'Brien et al 2001;MacKenzie and Iskra 2005).…”
Section: Introductionmentioning
confidence: 99%
“…During this time, N. ditissima and N. faginata were discovered in the UP and LP, respectively (O'Brien et al, 2001). The insect was established across much of eastern UP, northwestern LP, and a few of islands in the adjoining Great Lakes by 2009 (Wieferich et al, 2011).…”
Section: History and Spread Of Beech Bark Disease Agentsmentioning
confidence: 99%
“…Beech scale was observed in the Lower Peninsula (LP) of Michigan in 1990(O'Brien et al, 2001. By 2001, the insect was well established in parts of the Upper Pennisula (UP) and LP.…”
Section: History and Spread Of Beech Bark Disease Agentsmentioning
confidence: 99%
“…Breeding experiments were carried out at Ludington State Park, Ludington, Michigan, USA, where beech bark disease was first reported in 2000 (O'Brien et al 2001) and heavy levels of beech scale infestation are currently observed. Two infested trees (1506 and 1510) and two uninfested trees (1504 and 1505) were selected as parents for scale resistance studies.…”
Section: Study Area and Plant Materialsmentioning
confidence: 99%